GAMBARAN NILAI HASIL OSCE BLOK RRESPIRASI PADA MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS NEGERI GORONTALO - Septianingsi Katili; Muhamad Nur Syukriani Yusuf; Elen Lukum; Maimun Ihsan; Vivien Novarina A. Kasiem (Cahaya Ilmu Bangsa Institute, 2025)
Background: Clinical competence is one of the essential aspects that medical faculty graduates must master to provide quality health services. Evaluation of clinical skills through Objective Structured Clinical Examination (OSCE) is an important method in assessing student abilities, including in Respiratory Block, which discusses high-prevalence diseases such as asthma, tuberculosis, and COPD. This study aims to determine the description of the OSCE results of Respiratory Block in students of the Faculty of Medicine, Gorontalo State University. Method: This study uses a descriptive quantitative design, with 158 students from the 2020, 2021, and 2022 classes participating in total sampling. Data were obtained from OSCE score archives and analyzed descriptively. Results: Most students have scores in the 80-84 range. The class of 2022 achieved the highest average score (85.9), followed by the class of 2021 (85.4) and the class of 2020 (82.7). The class of 2022 also achieved the highest percentage of graduation without remedial (56.9%). Conclusion: Based on the final OSCE scores between batches each year, these results reflect improved student performance influenced by curriculum development and learning quality. This study provides input for future curriculum evaluation and development to support the optimal achievement of student clinical competence. This study is limited by a small sample, short period, and uncontrollable variables, so future research is expected to overcome this with a larger sample, more extended period, and more complex study design. Latar Belakang: Kompetensi klinis merupakan salah satu aspek esensial yang harus dikuasai oleh lulusan fakultas kedokteran untuk memberikan pelayanan kesehatan yang berkualitas. Evaluasi keterampilan klinis melalui Objective Structured Clinical Examination (OSCE) menjadi metode penting dalam menilai kemampuan mahasiswa, termasuk pada Blok Respirasi yang membahas penyakit berprevalensi tinggi seperti asma, tuberkulosis, dan PPOK. Penelitian ini bertujuan untuk mengetahui gambaran nilai hasil OSCE Blok Respirasi pada mahasiswa Fakultas Kedokteran Universitas Negeri Gorontalo. Metode : Penelitian ini bersifat menggunakan desain deskriptif kuantitatif dengan total sampling, melibatkan 158 mahasiswa dari angkatan 2020, 2021, dan 2022. Data diperoleh dari arsip nilai OSCE dan dianalisis secara deskriptif. Hasil: Mayoritas mahasiswa memiliki nilai pada rentang 80–84. Rata-rata nilai tertinggi dicapai oleh angkatan 2022 (85,9), diikuti angkatan 2021 (85,4), dan angkatan 2020 (82,7). Persentase kelulusan tanpa remedial tertinggi juga dicapai oleh angkatan 2022 (56,9%). Kesimpulan: Berdasarkan nilai akhir OSCE antarangkatan setiap tahunnya, hasil ini mencerminkan peningkatan kinerja mahasiswa, yang diduga dipengaruhi oleh pengembangan kurikulum dan kualitas pembelajaran. Penelitian ini memberikan masukan untuk evaluasi dan pengembangan kurikulum di masa mendatang untuk mendukung pencapaian kompetensi klinis mahasiswa secara optimal. Penelitian ini terbatas oleh sampel kecil, periode singkat, dan variabel tak terkendali, sehingga penelitian selanjutnya diharapkan dapat mengatasi hal tersebut dengan sampel lebih besar, periode lebih panjang, dan desain studi yang lebih kompleks.